Comparative Economic Analysis Between Endogenous and Recombinant Production of Hyaluronic Acid - Torres-Acosta, Mario A.; Castaneda-Aponte, Héctor M.; Mora-Galvez, Liliana M.; Gil-Garzon, Monica R.; Banda-Magaña, Martin P.; Marcellin, Esteban; Mayolo-Deloisa, Karla; Licona-Cassani, Cuauhtemoc (Frontiers in Bioengineering and Biotechnology, 2021)
Hyaluronic acid (HA) is a biopolymer with a wide range of applications, mainly in the cosmetic and pharmaceutical sectors. Typical industrial-scale production utilizes organisms that generate HA during their developmental cycle, such as Streptococcus equi sub. zooepidemicus. However, a significant disadvantage of using Streptococcus equi sub. zooepidemicus is that it is a zoonotic pathogen, which use at industrial scale can create several risks. This creates opportunities for heterologous, or recombinant, production of HA. At an industrial scale, the recovery and purification of HA follow a series of precipitation and filtration steps. Current recombinant approaches are developing promising alternatives, although their industrial implementation has yet to be adequately assessed. The present study aims to create a theoretical framework to forecast the advantages and disadvantages of endogenous and recombinant strains in production with the same downstream strategy. The analyses included a selection of the best cost-related recombinant and endogenous production strategies, followed by a sensitivity analysis of different production variables in order to identify the three most critical parameters. Then, all variables were analyzed by varying them simultaneously and employing multiple linear regression. Results indicate that, regardless of HA source, production titer, recovery yield and bioreactor scale are the parameters that affect production costs the most. Current results indicate that recombinant production needs to improve current titer at least 2-fold in order to compete with costs of endogenous production.. This study serves as a platform to inform decision-making for future developments and improvements in the recombinant production of HA.